ANALISIS TINGKAT RISIKO ERGONOMI MENGGUNAKAN METODE REBA TERHADAP KELUHAN MSDs PADA PENGRAJIN BATIK DI NISYA BATIK, KUNINGAN - Febi Abu Hanifah; Ekawati Ekawati; Siswi Jayanti; Yuliani Setyaningsih (Jurnal Kesehatan Masyarakat (Undip), 2017)
Nisya Batik is a batik industry that included to an Informal Industry Sector. One of the health risks that could possibly happen is Musculoskeletal Disorders (MSDs). This research is using Rapid Entire Body Assessment (REBA) method which analyzes body posture of a worker while working. There are 11 activities batik at Nisya Batik, including spreading a fabric, making  stamp pattern, taking paraffin with canting, covering stamp, making  mixture of fabric dye, pouring water into coloration’s tool, coloring fabric, draining fabric, boiling fabric, draining fabric and seasoning fabric. The body posture that scored by researcher is including neck posture, back posture, upper arm posture, lower arm posture, wrist posture and leg posture. This research is also describing subjective complaints of the worker who related to MSDs. The purpose of this research is to analyze Ergonomic Risk Level using REBA Method to the complaint of MSDs to batik craftsmen at Nisya Batik, Kuningan. This Research is a qualitative research using observational approach and interview. The observation is using observe work postur to a worker as a main informan and the interview is using to a worker and also to the Business owner as a triangulation informant. Based on observations result with using Rapid Entire Body Assessment (REBA), there are 9 percent (1 posture) with low risk (low risk); 64 percent (7 postures) with medium risk (medium risk); and 27 percent (3 postures) with high risk (high risk). There is a subjective complaint associated with MSDs worker felt like aches and pains. It can be concluded that the analysis of the risk level of ergonomics at Nisya Batik batik craftsmen in Kuningan varies with accompanying diverse subjective complaints.